2020
DOI: 10.1073/pnas.1911695117
|View full text |Cite
|
Sign up to set email alerts
|

Signing at the beginning versus at the end does not decrease dishonesty

Abstract: Honest reporting is essential for society to function well. However, people frequently lie when asked to provide information, such as misrepresenting their income to save money on taxes. A landmark finding published in PNAS [L. L. (2012)] provided evidence for a simple way of encouraging honest reporting: asking people to sign a veracity statement at the beginning instead of at the end of a self-report form. Since this finding was published, various government agencies have adopted this practice. However, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 14 publications
3
57
0
5
Order By: Relevance
“…As such, policy makers should think twice before implementing digital signatures, particularly those that require more effort and are detested by users. Given our null results and those of other signature honesty studies (Kettle et al 2017;Kristal et al 2020) a true effect is unlikely to exist. We therefore suggest not dedicating future research to signature interventions for honesty.…”
Section: Resultssupporting
(Expert classified)
See 2 more Smart Citations
“…As such, policy makers should think twice before implementing digital signatures, particularly those that require more effort and are detested by users. Given our null results and those of other signature honesty studies (Kettle et al 2017;Kristal et al 2020) a true effect is unlikely to exist. We therefore suggest not dedicating future research to signature interventions for honesty.…”
Section: Resultssupporting
(Expert classified)
“…Since conduction of our digital signature experiments, a series of signature replication experiments has been published (Kristal et al 2020). In line with our research and that of Kettle et al (2017), a signature honesty effect could not be replicated.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This problem is not unique to a particular field or subfield. It plagues all of the social sciences, including the field of consumer psychology (e.g., Kristal et al, 2020; Simmons & Nelson, 2019; Verschuere et al, 2018; Ziano et al, 2020).…”
Section: Why Pre‐register?mentioning
confidence: 99%
“…However, the notion that signing reduces unethicality by invoking moral values lacks additional empirical support. First, a more recent study failed to replicate the findings in a laboratory experiment (Kristal et al, 2020) and concluded that merely changing the position of a signature on a form (from bottom to top) does not, in itself, reduce dishonesty. Furthermore, the idea for the "signing-at-the-beginning" intervention relied also on a previous study by Mazar, Amir, and Ariely (2008), which claimed that asking people to recall the Ten Commandments reduced cheating in a similar laboratory task.…”
Section: Honesty Pledges For the Behaviorally-based Regulation Of Dishonesty Introductionmentioning
confidence: 99%